2003
DOI: 10.1016/s1286-4579(03)00025-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential properties of CBA/J mononuclear phagocytes recovered from an inflammatory site and probed with two different species of Leishmania

Abstract: While CBA/J mice fail to be permissive to Leishmania amazonensis-driven pathogenic processes, they heal easily following Leishmania major infection. The early-phase events are crucial to the outcome of Leishmania infection and it is known that macrophages (Mphi) are important in infection control. In the present study we investigated the role of Mphi in driving CBA/J susceptibility to L. amazonensis. We performed kinetic studies and compared the capacity of L. amazonensis and L. major to infect Mphi. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 51 publications
8
77
1
2
Order By: Relevance
“…Moreover, the same histopathological pattern was observed in CBA mice infected with L. amazonensis, but not with L. major (30), confirming the striking differences between New World and Old World Leishmania species. Additionally, when compared with L. major, L. amazonensis was highly resistant to NO-mediated leishmanicidal activity in murine macrophages in vitro (31,32), but Mukbel et al (32) found parasite killing to be dependent on superoxide production, in agreement with our findings. In parallel with New World leishmanial infection, killing of M. tuberculosis was shown to be NO-independent in human macrophages (33), and M. bovis bacterial load was significantly increased upon IFN-␣/␤ treatment (34).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the same histopathological pattern was observed in CBA mice infected with L. amazonensis, but not with L. major (30), confirming the striking differences between New World and Old World Leishmania species. Additionally, when compared with L. major, L. amazonensis was highly resistant to NO-mediated leishmanicidal activity in murine macrophages in vitro (31,32), but Mukbel et al (32) found parasite killing to be dependent on superoxide production, in agreement with our findings. In parallel with New World leishmanial infection, killing of M. tuberculosis was shown to be NO-independent in human macrophages (33), and M. bovis bacterial load was significantly increased upon IFN-␣/␤ treatment (34).…”
Section: Discussionsupporting
confidence: 91%
“…However, it has been reported that NO inhibition did not modify the course of L. amazonensis infection in vitro (42) or in vivo (24). Our results with L-NAME implicated NO as a major mediator of leishmanicidal activity of LTB 4 .…”
Section: Discussioncontrasting
confidence: 44%
“…It has been previously shown that macrophages from mice infected with L. major produce more TNF than do those from mice infected with L. amazonensis (Gomes et al 2003). Moreover, CBA mice produce less TNF when infected with L. amazonensis than when infected with L. major (Lemos de Souza et al 2000).…”
Section: Discussionmentioning
confidence: 97%